GAME INTERAKTIF WORDWALL PADA MATERI PERKEMBANGBIAKAN TUMBUHAN UNTUK MENDUKUNG MERDEKA BELAJAR SISWA SD - Estuhono, Estuhono; Anggrayni, Melisa; Sukmawati, Sukmawati (Jurnal Muara Pendidikan, 2024)
This research is motivated by the still not optimal use of learning media in science learning, especially material on plant reproduction. So, this research developed an interactive wordwall game media for science learning to overcome this problem. The purpose of this research is to develop an interactive wordwall game media for science learning, as well as to produce valid, practical and effective media. The type of research used in this research is research and development (R&D). This development procedure refers to the development of the ADDIE model, which consists of several stages, namely (1) Analysis Phase, (2) Design Stage, (3) Development Stage; after going through the development stage a validation test is carried out by 3 validators with 80% results (4) Implementation Stage, at this stage practicality tests were carried out by practitioners (teachers) and (students) with 82% results after that a video media trial was carried out with an effectiveness sheet to get 76% results by obtaining student learning outcomes, (5) Evaluation Stage (Evaluation). Based on the ADDIE procedure used in the research above, it can be concluded that the Wordwall interactive game researchers developed is feasible because it meets the minimum valid, practical and effective criteria.